Renewable Energy Systems for Building Designers Fundamentals of Net Zero and High Performance Design (Taylor & Francis, 2024)
Building; Design; Designers; Dorothy; Energy; for; Fundamentals; Gerring; High; Net; of; Performance; Renewable; Systems; Zero
English
Keywords: Alternative & renewable energy sources & technology; Building construction & materials; Civil engineering, surveying & building; Environmentally-friendly architecture & design; Building; Design; Designers; Dorothy; Energy; for; Fundamentals; Gerring; High; Net; of; Performance; Renewable; Systems; Zero